Relationship Between Digital Marketing Communication And Consumer Purchase Decision Process, A Research On Smart Devices - Erzurumlu, Sibel (International Journal of Contemporary Economics and Administrative Sciences, 2024)
Abstract Digital marketing has changed people's habits of accessing information, determined their interactions, and provided the birth of various new marketing technologies. Along with these changes in the digital environment, there have also been some changes in consumer purchasing behaviors. Now consumers also use technology very effectively when making purchasing decisions. Understanding how consumers behave in these purchasing decision processes and what affects these processes has become important in the field of marketing. In addition, in recent years, marketers have increasingly included studies on how different generations use technology. This research aims to show how marketing activities carried out in the digital environment in the smart device sector affect the consumer purchasing decision process and the differences between genders and generations. A survey study was conducted on 281 social media users over the age of 18 living in Istanbul using the convenience sampling method, and the data were analyzed. The research reveals that digital marketing activities are effective in consumer purchasing decision processes, and that this effect exists regardless of gender and generation.